Possible transmission routes of Vibrio spp. in tropical cage-cultured marine fishes - Mohamad, Nurliyana; Azmai, Mohammad Noor Amal; Saad, Mohd Zamri; Md Yasin, Ina Salwany (Wiley-Blackwell Publishing Ltd., 2019)
This study investigates the possible transmission routes of Vibrio spp. in a tropical cage-cultured marine fishes. Samplings of cultured Asian seabass, red snapper, hybrid grouper, wild fish, trash fish, fish fry, water and sediment samples were conducted from December 2016 to August 2017. All fish were dissected in situ and swabs were taken aseptically from the skin, eye, liver and kidney for bacterial isolation and identification. Bacterial isolation and identification from water, sediment and trash fish were also made. A total of 261 Vibrio spp. isolates recovered from the cultured, wild and fry fish, as well as from the sediment and water of the farm environment were analysed. Sequences of the pyrH gene were used to investigate the degree of relatedness and possible transmission routes existing between the isolated Vibrio spp. The population tree revealed the existence of selected Vibrio spp. that possibly transmitted between the newly introduced fish fry and wild fish into the cultured fish, while water also might possibly serves as natural transmission medium of certain Vibrio spp. in this fish farm.